Exosomes transport trace amounts of (poly)phenols. Issue 9 (18th August 2020) - Arola-Arnal, Anna; López de las Hazas, María-Carmen; Iglesias-Carres, Lisard; Mantilla-Escalante, Diana C.; Suárez, Manuel; Busto, Rebeca; Visioli, Francesco; Bladé, Cinta; Dávalos, Alberto
Abstract : Grape seed polyphenol extract-derived (poly)phenols are minimally, if any, transported by exosomes. Abstract : (Poly)phenols have varied biological activities that may account for the beneficial effects of fruits and vegetables as part of a healthy diet. Although their cellular absorption and their many mechanisms of action have been partly elucidated, their transport through the systemic circulation, other than their binding to albumin, is poorly described. We aimed at determining whether (poly)phenols can be transported by extracellular vesicles. We supplemented rats with a dietary grape seed polyphenol extract (GSPE) and we quantified (poly)phenols and their metabolites at 3 and 7 h post-gavage. After quantitative LC-MS/MS analysis of circulating aglycones, and microbial-derived, or phase II-derived metabolites we recorded a quantitatively very modest transport of (poly)phenols in plasma exosomes when isolated by commercial ultracentrifugation or precipitation kits. Our data suggest that GSPE-derived (poly)phenols are minimally, if at all, transported by exosomes.